"influence of trust as an extended factor towards cash on delivery in e-commerce company PT.jujual " (Journal of Business and Management, 2022)
In this modern era, the success of an e-commerce cannot be separated from the importance of the interest of their customer to use their application, in this case it would be their behavioral intention. An e-commerce is also demanded to always innovate whether it by creating or adopting old concepts such as a Cash On Delivery payment method. In this research the author assumes that Trust, Perceived Usefulness, and Perceived Ease of Use can have a good impact on Customer’s attitude towards using a technology that would then affect their behavioral intention towards using the technology. Therefore, to prove it, the author tries to conduct the research in PT.JUJUAL by using Technology acceptance model with an addition of Trust as an external variable and analyzing them using Path Analysis tools to find out why the customers would not accept the technology of Cash On Delivery payment method in PT.JUJUAL. The purpose of this study aims to examine the relationship between perceived Usefulness, perceived ease of use, trust, attitude and Customers intention toward using COD as a payment method. The methodology in this study uses quantitative data where the author collects primary data from several main cities where the COD campaign is active, which consist of 200 respondents. Findings show that Perceived Usefulness, Perceived Ease of Use and Attitude are jointly responsible in determining the users’ intention to use of COD payment method. Trust was found as a key factor influences users’ intention to use COD payment method. Consideration of the factors identified should lead to more successful COD adoption.(Technology Acceptance Model, Perceived Usefulness, Perceived Ease of Use, Trust, Attitude, Behavioral Intention, E-commerce. Path Analysis.)